Seismic microzoning of Štip in Macedonia. Issue 98 (July 2017) - Lee, V.W.; Trifunac, M.D.; Bulajić, B.Đ.; Manić, M.I.; Herak, D.; Herak, M.; Dimov, G.; Gičev, V.
Abstract: Seismic microzonation maps for Štip (Macedonia) and its surroundings are presented based on the uniform-hazard-spectrum (UHS) methodology. Such mapping satisfies the guidelines for performance-based design (PBD), which requires specification of two sets of spectral amplitudes—one for which the structure will remain essentially linear, and the other for which it will undergo a nonlinear response. The UHS method also enables us to include contributions from excitation by large distant earthquakes as well as the simultaneous effects of site geology and site soils. Thus, the maps we present include, in a balanced way, the effects of near and distant large earthquakes, spatial distribution of seismic activity, the site geology, and the site soil properties. Highlights: Microzonation maps, which include a description of site geology and site soil. Contribution of large distant earthquakes to long period design spectra. Mapping hazard for earthquakes with different attenuation laws. Application of Uniform Hazard Spectra method to seismic microzonation.